The Influence of Family Environmental and Entrepreneurship Education on Interest in Entrepreneurship with Self Efficacy as a Mediation Variable in Sharia Business Perspective (Study on Students of the Faculty of Economics and Islamic Business UIN Raden In - Zuliansyah, A; Pratomo, Dimas; Triyana Meifa, Yolla (KnE Social Sciences, 2024)
The research investigates the influence of family environment and entrepreneurship education on interest in entrepreneurship with self-efficacy as a mediating variable from a Sharia business perspective. This research uses a quantitative approach with a sample size of 129 respondents. The research results show that all independent variables have a significant effect on interest in entrepreneurship. The self-efficacy variable can mediate the influence of business capital on interest in entrepreneurship among FEBI UIN Raden Intan Lampung students and entrepreneurship education on interest in entrepreneurship among FEBI UIN Raden Intan Lampung students. It can be concluded that the application of business capital, entrepreneurship education, Self-efficacy, and interest in entrepreneurship from a Sharia business perspective is very good. Keywords: Business Capital, Entrepreneurship Education, Self-Efficacy, Interest in Entrepreneurship.